Management of keratocystic odontogenic tumor in the maxillary sinus of 12-year-old children: A case report - Hendy U. Suhandi; Yudy A. Utomo; Eky Nasuri; Vera Julia (Journal of Dentomaxillofacial Science, 2021)
Objective: Keratocystic odontogenic tumor (KCOT) is a benign intraosseous tumor of odontogenic origin, making up the third most common odontogenic cyst. KCOTs arise from the remnants of dental lamina or the basal cells of the overlying oral epithelium. KCOTs are characterized by an aggressive behaviour with a relatively high recurrence rate, especially if they are associated with syndromes. Treatment of KCOTs include marsupialization, saucerization, Methods: A 12-year-old child patient was referred to the Specialist Clinic of Oral and Maxillofacial Surgery, Cipto Mangkusumo Hospital. On physical examination, facial asymmetry, a fixated swelling and lump in right maxilla from the second molar to canine with tenderness were observed. A complete history was taken and clinical examination followed by complete enucleation with sulcular flap from 12 region until 18 regions was performed. The diagnosis was maxillary dentigerous cyst based on histopathological result after the operation. Results: The medical history was not significant and patient was in a generally good condition with no fever, nausea, pain, or difficulty in breathing. Extra oral examination showed facial asymmetry and visible lump in the right region of the maxilla. Conclusion: The diagnosis of maxillary KCOT expanding to maxillary sinus can be achieved with adequate datas; history, clinical, and histopathological examinations. Careful surgical approach and proper treatment decision is crucial to avoid complications according to individual case of each patient, especially in children.